Production and preparation process of chromatographic-grade tetrahydrofuran
Through the catalytic and adsorption technology of modified carbon nanotube-supported heteropoly acids and chitosan-supported activated carbon, the problem of low yield and low purity in the prior art was solved, and high efficiency and low cost chromatographic tetrahydrofuran preparation was achieved. Improves the accuracy and reliability of chromatographic analysis.
Patent Information
- Application Number
- CN202510012016.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as low yield, low purity, complex equipment, high energy consumption and easy catalyst loss when preparing tetrahydrofuran, resulting in high costs and technology being restrained by foreign countries.
Modified carbon nanotube-supported heteropolyacid was used as a catalyst, and a highly active adsorbent was formed through chitosan-supported activated carbon. The chromatographic tetrahydrofuran was prepared by combining catalytic and adsorption treatment under high temperature and high pressure conditions.
It improves the yield and purity of tetrahydrofuran, reduces production costs, enhances the high temperature and high pressure resistance and reusability of the catalyst, and improves the accuracy and reliability of chromatographic analysis.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chromatographic reagent preparation, and in particular relates to a production and preparation process of chromatographic grade tetrahydrofuran. Background Art
[0002] As an excellent liquid chromatography reagent, tetrahydrofuran has the characteristics of fast dissolution and good permeation and diffusion properties. It is widely used in paper chromatography of amino acids and peptides, ultraviolet spectrophotometer, high performance liquid chromatography analysis and quantitative analysis of food vitamin K1.
[0003] The existing industrial production methods of tetrahydrofuran include: maleic anhydride catalytic hydrogenation method, dichlorobutene method, butadiene oxidation method and 1,4-butanediol dehydration method. Among them, the 1,4-butanediol dehydration method is to make 1,4-butanediol (BDO) dehydrate under acid catalysis to produce tetrahydrofuran. Compared with other methods, this method is simple, mature, and has the characteristics of low reaction temperature and high yield. The 1,4-butanediol method can be divided into gas phase method and liquid phase method. The gas phase method is conducive to the preparation of multiple products. The catalyst mostly uses silica gel and molecular sieve. The conversion rate of 1,4-butanediol can be as high as 99%, but the reaction equipment is relatively complex, the reaction energy consumption is high, and the initial investment is high. The catalyst for preparing tetrahydrofuran by the liquid phase 1,4-butanediol method mostly uses concentrated sulfuric acid, ion exchange resin, heteropoly acid, etc. Concentrated sulfuric acid is corrosive to equipment and the product is difficult to separate; resin catalysts have good low-temperature catalytic effects, but are not resistant to high temperatures and have high investment costs; heteropolyacid catalysts are easily soluble in polar solvents, active components are easily lost and difficult to recover, and have a low specific surface area, which is not conducive to exerting the advantages of heteropolyacids.
[0004] The production of tetrahydrofuran produced in China is currently low and its purity is not high. High-purity tetrahydrofuran is mostly imported, resulting in high costs and being greatly restricted by foreign technology.
[0005] Based on this, we proposed a production and preparation process of chromatographic grade tetrahydrofuran, hoping to solve the shortcomings of the existing technology. Summary of the invention
[0006] The purpose of the invention is to provide a production and preparation process of chromatographic grade tetrahydrofuran in view of the existing problems.
[0007] The present invention is achieved through the following technical solutions: A production process for chromatographic grade tetrahydrofuran comprises the following steps: S1. Add 1,4-butanediol and catalyst into a round-bottom flask, install a short distillation column, stir magnetically, heat in an oil bath at 160-200°C, and evaporate the crude product while reacting; S2, washing the crude product obtained in step S1 with a sodium chloride aqueous solution and separating the organic layer liquid; S3, passing the organic layer liquid obtained in step S2 into an adsorbent column filled with an adsorbent for adsorption treatment to obtain chromatographic grade tetrahydrofuran.
[0008] Preferably, the preparation of the catalyst described in step S1 comprises the following steps: (1) Add carbon nanotubes to a three-necked flask, then add concentrated sulfuric acid and concentrated nitric acid to the three-necked flask in a volume ratio of 1 to 3:1, disperse evenly with ultrasound, condense and reflux in a constant temperature water bath at 80 to 100 ° C for 9 to 13 hours, cool to room temperature, add 3 to 5 times the volume of deionized water to dilute, stir and mix, centrifuge at 3000 to 5000 rpm for 16 to 20 minutes, wash with deionized water until neutral, and filter. Place the obtained solid in a vacuum drying oven and dry at 60 to 70 ° C to constant weight to obtain carboxylated carbon nanotubes for use; (2) Add 2,6-di-tert-butyl-4-aminophenol to anhydrous ethanol for ultrasonic dispersion, then add N,N-dimethylbenzylamine, continue ultrasonic dispersion until uniform, then heat to 50-70°C, add allyl isothiocyanate while stirring, stir at constant temperature for 5-6 hours, cool to room temperature, wash with water 3-5 times, place in a vacuum drying oven, dry at 30-40°C to constant weight to obtain hindered phenol for use; (3) adding carboxylated carbon nanotubes and hindered phenol into a reactor at a ratio of 1:1-3, reacting at 120-150°C for 0.5-1h, and obtaining modified carbon nanotubes for use; (4) The modified carbon nanotubes are uniformly dispersed in anhydrous ethanol, and then heteropoly acid is added, and the mixture is immersed at 50-60°C for 2-4 hours, and then dispersed for 30-50 minutes. The mixture is then placed in a rotary evaporator and subjected to rotary evaporation at 30-40°C. After most of the solvent is evaporated, the mixture is placed in a vacuum drying oven and dried at 30-40°C to constant weight to obtain the catalyst.
[0009] Preferably, the weight-to-volume ratio of the carbon nanotubes to the acid mixture in step (1) is 1 g:120-150 mL.
[0010] Preferably, the mass ratio of 2,6-di-tert-butyl-4-aminophenol, N,N-dimethylbenzylamine and allyl isothiocyanate in step (2) is 1:0.05-0.09:1-2.
[0011] Preferably, the mass volume ratio of the modified carbon nanotubes to anhydrous ethanol in step (4) is 1 g: 30-50 mL; The mass volume ratio of the modified carbon nanotubes to the heteropoly acid aqueous solution is 1 g:30-40 mL.
[0012] Preferably, the heteropolyacid in step (4) is a Dawson structure heteropolyacid.
[0013] Preferably, the method for preparing the adsorbent described in step S3 comprises the following steps: (1) Add chitosan to 1% acetic acid solution, stir until chitosan is completely dissolved, add activated carbon, stir at 80-90°C for 3-4 hours, let stand and filter, and then deep-cold grind at -80--20°C to obtain activated carbon-loaded chitosan composite for use; (2) Add the above activated carbon-loaded chitosan composite to isopropanol, raise the temperature to 80-90°C while stirring, add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, stir at constant temperature for 5-9 hours, filter, wash with anhydrous ethanol 3-5 times, filter, place in a vacuum drying oven, dry at 50-60°C to constant weight, and obtain the modified composite for use; (3) Dissolve acetamide and soybean lecithin in anhydrous ethanol at a weight ratio of 1:4-5 and mix well. Heat to 50-60°C and add the modified composite agent. Stir at constant temperature for 2-3 hours, filter and dry under vacuum at 30-40°C to obtain the adsorbent.
[0014] Preferably, the weight volume ratio of chitosan to 1% acetic acid in step (1) is 1-2 g:100 mL; The weight ratio of chitosan to activated carbon is 1:40~100.
[0015] Preferably, the mass volume ratio of the activated carbon-loaded chitosan composite to isopropanol in step (2) is 1 g: 12-18 mL; The mass ratio of the activated carbon-loaded chitosan composite agent to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.3-0.5.
[0016] Preferably, the mass volume ratio of acetamide to anhydrous ethanol in step (3) is 1 g: 20-40 mL; The weight ratio of the acetamide to the modified composite agent is 1:80-120.
[0017] Compared with the prior art, the present invention has the following advantages: In the preparation of chromatographic-grade tetrahydrofuran, the present invention sequentially reacts 2,6-di-tert-butyl-4-aminophenol with N,N-dimethylbenzylamine and allyl isothiocyanate to obtain hindered phenol; reacts carboxylated carbon nanotubes with hindered phenol to obtain modified carbon nanotubes; and then loads a heteropolyacid aqueous solution into the modified carbon nanotubes to obtain a supported catalyst, which exhibits good catalytic performance and performance stability under high temperature and high pressure conditions. Chitosan is cross-linked to the surface of activated carbon, and then reacts with 3-chloro-2-hydroxypropyltrimethylammonium chloride to form a quaternary ammonium salt, and then an activation treatment is performed to obtain a high-activity adsorbent with stable performance and can be repeatedly used.
[0018] First, 2,6-di-tert-butyl-4-aminophenol is reacted with N,N-dimethylbenzylamine and allyl isothiocyanate in sequence to obtain hindered phenol, which is then introduced into carbon nanotubes to modify the oxides on the surface of the carbon nanotubes, increase the oxidation current, and the allyl group can form a stable chemical bond with the carboxylated carbon nanotubes through chemical reactions, thereby achieving chemical modification and functionalization of the carbon nanotubes. Through this modification, the carbon nanotubes can be used as a carrier of the catalyst, providing a reaction site and an electron channel, thereby improving the loading effect. In addition, the modified catalyst exhibits better catalytic performance under high temperature and high pressure conditions. Then, the heteropoly acid catalyst is loaded into the modified carbon nanotubes to effectively avoid the problem of easy loss of the active components of the heteropoly acid catalyst, further improve the catalytic activity and high temperature and high pressure resistance of the catalyst, and can be reused repeatedly, which is more energy-saving and environmentally friendly.
[0019] Secondly, the chitosan and activated carbon surfaces are cross-linked under acidic conditions, and then reacted with an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride to generate a quaternary ammonium salt that can effectively adsorb impurities such as moisture, carbon dioxide, and methanol. After being treated with acetamide and soy lecithin, the surface activity of the adsorbent is improved, thus forming a structurally stable and reusable high-efficiency adsorbent.
[0020] Finally, the above catalyst and adsorbent are used in the preparation and purification of tetrahydrofuran, which not only effectively improves the yield and purity of tetrahydrofuran, but also improves its transmittance, thereby improving the accuracy, reliability and efficiency of chromatographic analysis, thereby obtaining high-quality chromatographic-grade tetrahydrofuran. In addition, the present invention provides a production and preparation idea for chromatographic-grade tetrahydrofuran, and the catalyst and adsorbent provided by the present invention can be used in multiple fields and have good added value. DETAILED DESCRIPTION
[0021] In order to further explain the present invention, it is described below in conjunction with the following specific embodiments. Example 1
[0022] A production process for chromatographic grade tetrahydrofuran comprises the following steps: S1. Add 1,4-butanediol and catalyst into a round-bottom flask, install a short distillation column, stir magnetically, heat in an oil bath at 160°C, and evaporate the crude product while reacting; S2, washing the crude product obtained in step S1 with a sodium chloride aqueous solution and separating the organic layer liquid; S3, passing the organic layer liquid obtained in step S2 into an adsorbent column filled with an adsorbent for adsorption treatment to obtain chromatographic grade tetrahydrofuran; The preparation of the catalyst described in step S1 comprises the following steps: (1) Add carbon nanotubes to a three-necked flask, then add concentrated sulfuric acid and concentrated nitric acid to the three-necked flask in a volume ratio of 1:1, disperse evenly by ultrasonication, condense and reflux in a constant temperature water bath at 80°C for 9 hours, cool to room temperature, add 3 times the volume of deionized water to dilute, stir and mix, centrifuge at 3000 rpm for 16 minutes, wash with deionized water until neutral, and filter. Place the obtained solid in a vacuum drying oven and dry at 60°C to constant weight to obtain carboxylated carbon nanotubes for use; The weight-to-volume ratio of the carbon nanotubes to the acid mixture is 1 g:120 mL; (2) Add 2,6-di-tert-butyl-4-aminophenol to anhydrous ethanol for ultrasonic dispersion, then add N,N-dimethylbenzylamine, continue ultrasonic dispersion until uniform, then heat to 50°C, add allyl isothiocyanate while stirring, stir at constant temperature for 5 hours, cool to room temperature, wash with water three times, place in a vacuum drying oven, dry at 30°C to constant weight to obtain hindered phenol for use; The mass ratio of 2,6-di-tert-butyl-4-aminophenol, N,N-dimethylbenzylamine and allyl isothiocyanate is 1:0.05:1; (3) adding carboxylated carbon nanotubes and hindered phenol into a reactor in a ratio of 1:1, reacting at 120°C for 0.5h to obtain modified carbon nanotubes for later use; (4) The modified carbon nanotubes are uniformly dispersed in anhydrous ethanol, the mass volume ratio of the modified carbon nanotubes to the anhydrous ethanol is 1g:30mL, and then a phosphotungstic acid aqueous solution is added, the mass volume ratio of the modified carbon nanotubes to the phosphotungstic acid aqueous solution is 1g:30mL, and then immersed at 50°C for 2h, and then dispersed for 30min, and then placed in a rotary evaporator, and subjected to rotary evaporation at 30°C. After evaporating most of the solvent, the catalyst is placed in a vacuum drying oven and dried at 30-40°C to constant weight to obtain a catalyst; The method for preparing the adsorbent described in step S3 comprises the following steps: (1) Add chitosan to 1% acetic acid solution, the weight volume ratio of chitosan to 1% acetic acid is 1g:100mL, stir until chitosan is completely dissolved, add activated carbon 40 times the weight of chitosan, stir at 80°C for 3h, let stand and filter, and then deep-cold grind at -80°C to obtain activated carbon-loaded chitosan composite for use; (2) Add the above-mentioned activated carbon-loaded chitosan composite to isopropanol, the mass volume ratio of the activated carbon-loaded chitosan composite to isopropanol is 1g:12mL, and heat to 80°C while stirring, then add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, the mass ratio of the activated carbon-loaded chitosan composite to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.3, stir at constant temperature for 5-9h, filter, wash with anhydrous ethanol 3 times, filter, and then place in a vacuum drying oven, dry at 50°C to constant weight to obtain the modified composite for use; (3) Acetamide and soybean lecithin were dissolved in anhydrous ethanol at a weight ratio of 1:4 and mixed. The mass volume ratio of acetamide to anhydrous ethanol was 1 g:20 mL. The temperature was raised to 50°C and the above-mentioned modified composite agent was added. The weight ratio of acetamide to the modified composite agent was 1:80. After constant temperature stirring for 2 h, the mixture was filtered and vacuum dried at 30°C to obtain the adsorbent. Example 2
[0023] A production process for chromatographic grade tetrahydrofuran comprises the following steps: S1. Add 1,4-butanediol and catalyst into a round-bottom flask, install a short distillation column, stir magnetically, heat in an oil bath at 180°C, and evaporate the crude product while reacting; S2, washing the crude product obtained in step S1 with a sodium chloride aqueous solution and separating the organic layer liquid; S3, passing the organic layer liquid obtained in step S2 into an adsorbent column filled with an adsorbent for adsorption treatment to obtain chromatographic grade tetrahydrofuran; The preparation of the catalyst described in step S1 comprises the following steps: (1) Add carbon nanotubes to a three-necked flask, then add concentrated sulfuric acid and concentrated nitric acid to the three-necked flask in a volume ratio of 2:1, disperse evenly by ultrasonication, condense and reflux in a 90°C constant temperature water bath for 11 hours, cool to room temperature, add 4 times the volume of deionized water to dilute, stir and mix, centrifuge at 4000 rpm for 18 minutes, wash with deionized water until neutral, and filter. Place the obtained solid in a vacuum drying oven and dry at 65°C to constant weight to obtain carboxylated carbon nanotubes for use; The weight-to-volume ratio of the carbon nanotubes to the acid mixture is 1 g:135 mL; (2) Add 2,6-di-tert-butyl-4-aminophenol to anhydrous ethanol for ultrasonic dispersion, then add N,N-dimethylbenzylamine, continue ultrasonic dispersion until uniform, then heat to 60°C, add allyl isothiocyanate while stirring, stir at constant temperature for 5.5 hours, cool to room temperature, wash with water 4 times, place in a vacuum drying oven, dry at 35°C to constant weight to obtain hindered phenol for use; The mass ratio of 2,6-di-tert-butyl-4-aminophenol, N,N-dimethylbenzylamine and allyl isothiocyanate is 1:0.07:1.5; (3) adding carboxylated carbon nanotubes and hindered phenol into a reactor at a ratio of 1:1.5, reacting at 135°C for 0.75h to obtain modified carbon nanotubes for later use; (4) The modified carbon nanotubes are uniformly dispersed in anhydrous ethanol, the mass volume ratio of the modified carbon nanotubes to the anhydrous ethanol is 1g:40mL, and then a phosphotungstic acid aqueous solution is added, the mass volume ratio of the modified carbon nanotubes to the phosphotungstic acid aqueous solution is 1g:35mL, and the mixture is immersed at 55°C for 3h, and then dispersed for 40min, and then placed in a rotary evaporator and subjected to rotary evaporation at 35°C. After evaporating most of the solvent, the mixture is placed in a vacuum drying oven and dried at 35°C to constant weight to obtain a catalyst; The method for preparing the adsorbent described in step S3 comprises the following steps: (1) Add chitosan to 1% acetic acid solution, the weight volume ratio of chitosan to 1% acetic acid is 1.5g:100mL, stir until chitosan is completely dissolved, add activated carbon 70 times the weight of chitosan, stir at 85°C for 3.5h, let stand and filter, and then deep-cold grind at -50°C to obtain activated carbon-loaded chitosan composite for use; (2) Add the above activated carbon-loaded chitosan composite to isopropanol, the mass volume ratio of the activated carbon-loaded chitosan composite to isopropanol is 1g:15mL, and heat to 85°C while stirring, then add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, the mass ratio of the activated carbon-loaded chitosan composite to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.4, stir at constant temperature for 7h, filter, wash with anhydrous ethanol 4 times, filter, and place in a vacuum drying oven, dry at 55°C to constant weight to obtain the modified composite for use; (3) Acetamide and soybean lecithin were dissolved in anhydrous ethanol at a weight ratio of 1:4.5 and mixed. The mass volume ratio of acetamide to anhydrous ethanol was 1 g:30 mL. The temperature was raised to 55°C and the above-mentioned modified composite agent was added. The weight ratio of acetamide to the modified composite agent was 1:100. After constant temperature stirring for 2.5 h, the mixture was filtered and vacuum dried at 35°C to obtain the adsorbent. Example 3
[0024] A production process for chromatographic grade tetrahydrofuran comprises the following steps: S1. Add 1,4-butanediol and catalyst into a round-bottom flask, install a short distillation column, stir magnetically, heat in an oil bath at 160-200°C, and evaporate the crude product while reacting; S2, washing the crude product obtained in step S1 with a sodium chloride aqueous solution and separating the organic layer liquid; S3, passing the organic layer liquid obtained in step S2 into an adsorbent column filled with an adsorbent for adsorption treatment to obtain chromatographic grade tetrahydrofuran; The preparation of the catalyst described in step S1 comprises the following steps: (1) Add carbon nanotubes to a three-necked flask, then add concentrated sulfuric acid and concentrated nitric acid to the three-necked flask in a volume ratio of 3:1, disperse evenly by ultrasonication, condense and reflux in a 100°C constant temperature water bath for 13 h, cool to room temperature, add 5 times the volume of deionized water to dilute, stir and mix, centrifuge at 5000 rpm for 20 min, wash with deionized water until neutral, and filter. Place the obtained solid in a vacuum drying oven and dry at 70°C to constant weight to obtain carboxylated carbon nanotubes for use; The weight-to-volume ratio of the carbon nanotubes to the acid mixture is 1 g:150 mL; (2) Add 2,6-di-tert-butyl-4-aminophenol to anhydrous ethanol for ultrasonic dispersion, then add N,N-dimethylbenzylamine, continue ultrasonic dispersion until uniform, then heat to 70°C, add allyl isothiocyanate while stirring, stir at constant temperature for 6 hours, cool to room temperature, wash with water 5 times, place in a vacuum drying oven, dry at 40°C to constant weight to obtain hindered phenol for use; The mass ratio of 2,6-di-tert-butyl-4-aminophenol, N,N-dimethylbenzylamine and allyl isothiocyanate is 1:0.09:2; (3) adding carboxylated carbon nanotubes and hindered phenol into a reactor at a ratio of 1:3, reacting at 150°C for 1 hour to obtain modified carbon nanotubes for later use; (4) The modified carbon nanotubes are uniformly dispersed in anhydrous ethanol, the mass volume ratio of the modified carbon nanotubes to the anhydrous ethanol is 1g:50mL, and then a phosphotungstic acid aqueous solution is added, the mass volume ratio of the modified carbon nanotubes to the phosphotungstic acid aqueous solution is 1g:40mL, and the mixture is immersed at 60°C for 4h, and then dispersed for 50min, and then placed in a rotary evaporator, and subjected to rotary evaporation at 40°C. After evaporating most of the solvent, the mixture is placed in a vacuum drying oven and dried at 40°C to constant weight to obtain a catalyst; The method for preparing the adsorbent described in step S3 comprises the following steps: (1) Add chitosan to 1% acetic acid solution, the weight volume ratio of chitosan to 1% acetic acid is 2g:100mL, stir until chitosan is completely dissolved, add activated carbon 100 times the weight of chitosan, stir at 90°C for 4h, let stand and filter, and then deep-cryogenically grind at -20°C to obtain activated carbon-loaded chitosan composite for use; (2) Add the above activated carbon-loaded chitosan composite to isopropanol, the mass volume ratio of the activated carbon-loaded chitosan composite to isopropanol is 1g:18mL, and heat to 90°C while stirring, then add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, the mass ratio of the activated carbon-loaded chitosan composite to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.5, stir at constant temperature for 9 hours, filter, wash with anhydrous ethanol 5 times, filter, and then place in a vacuum drying oven, dry at 60°C to constant weight to obtain the modified composite for use; (3) Acetamide and soybean lecithin were dissolved in anhydrous ethanol at a weight ratio of 1:5 and mixed evenly. The mass volume ratio of acetamide to anhydrous ethanol was 1 g:40 mL. The temperature was raised to 60°C and the above-mentioned modified composite agent was added. The weight ratio of acetamide to the modified composite agent was 1:120. After constant temperature stirring for 3 h, the mixture was filtered and vacuum dried at 40°C to obtain the adsorbent.
[0025] Comparative Example 1 Compared with Example 2, the only difference between Comparative Example 1 and Example 2 is the catalyst, and the rest of the technical solutions are consistent with those of Example 2.
[0026] The preparation of the catalyst of Comparative Example 1 comprises the following steps: (1) Add carbon nanotubes to a three-necked flask, then add concentrated sulfuric acid and concentrated nitric acid to the three-necked flask in a volume ratio of 2:1, disperse evenly by ultrasonication, condense and reflux in a 90°C constant temperature water bath for 11 hours, cool to room temperature, add 4 times the volume of deionized water to dilute, stir and mix, centrifuge at 4000 rpm for 18 minutes, wash with deionized water until neutral, and filter. Place the obtained solid in a vacuum drying oven and dry at 65°C to constant weight to obtain carboxylated carbon nanotubes for use; The weight-to-volume ratio of the carbon nanotubes to the acid mixture is 1 g:135 mL; (2) The above-mentioned carboxylated carbon nanotubes are uniformly dispersed in anhydrous ethanol, and the mass volume ratio of carboxylated carbon nanotubes to anhydrous ethanol is 1g:40mL. Then, a phosphotungstic acid aqueous solution is added, and the mass volume ratio of carboxylated carbon nanotubes to phosphotungstic acid aqueous solution is 1g:35mL. The mixture is immersed at 55°C for 3h, and then dispersed for 40min. The mixture is then placed in a rotary evaporator and subjected to rotary evaporation at 35°C. After most of the solvent is evaporated, the mixture is placed in a vacuum drying oven and dried at 35°C to constant weight to obtain the catalyst.
[0027] Comparative Example 2 Compared with Example 2, the only difference in this comparative example 2 is the catalyst, and the rest of the technical solutions are consistent with those of Example 2.
[0028] The preparation method of the catalyst of Comparative Example 2 is as follows: carbon nanotubes are uniformly dispersed in anhydrous ethanol, the mass volume ratio of carbon nanotubes to anhydrous ethanol is 1g:40mL, and then a phosphotungstic acid aqueous solution is added, the mass volume ratio of carbon nanotubes to the phosphotungstic acid aqueous solution is 1g:35mL, immersion treatment at 55°C for 3h, and then dispersion treatment for 40min, and then placed in a rotary evaporator, and rotary evaporation treatment is performed at 35°C. After evaporating most of the solvent, it is placed in a vacuum drying oven and dried at 35°C to constant weight to obtain the catalyst.
[0029] Comparative Example 3 Compared with Example 2, the catalyst in Comparative Example 3 is replaced with phosphotungstic acid, and the rest of the technical scheme is consistent with the technical scheme of Example 2.
[0030] Comparative Example 4 Compared with Example 2, the only difference in this comparative example 4 is the adsorbent, and the rest of the technical solutions are consistent with those of Example 2.
[0031] The preparation method of the adsorbent of this comparative example 4 is as follows: chitosan is added to 1% acetic acid solution, the weight volume ratio of chitosan to 1% acetic acid is 1.5g:100mL, and after stirring until the chitosan is completely dissolved, activated carbon 70 times the weight of the chitosan is added, and after stirring at 85°C for 3.5h, the mixture is allowed to stand and filtered, and then deep-cold crushed at -50°C to obtain the adsorbent.
[0032] Comparative Example 5 Compared with Example 2, the only difference in this comparative example 5 is the adsorbent, and the rest of the technical solutions are consistent with those of Example 2.
[0033] The preparation of the adsorbent in this comparative example 5 comprises the following steps: (1) Add chitosan to 1% acetic acid solution, the weight volume ratio of chitosan to 1% acetic acid is 1.5g:100mL, stir until chitosan is completely dissolved, add activated carbon 70 times the weight of chitosan, stir at 85°C for 3.5h, let stand and filter, and then deep-cold grind at -50°C to obtain activated carbon-loaded chitosan composite for use; (2) The activated carbon-loaded chitosan composite is added to isopropanol in a mass volume ratio of 1 g:15 mL. After heating to 85°C while stirring, an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride is added in a mass ratio of 1:0.4 to the activated carbon-loaded chitosan composite. After stirring at a constant temperature for 7 hours, the mixture is filtered, washed with anhydrous ethanol for 4 times, and then filtered. The mixture is placed in a vacuum drying oven and dried at 55°C to constant weight to obtain the adsorbent.
[0034] Comparative Example 6 Compared with Example 2, the adsorbent in Comparative Example 6 is replaced with activated carbon, and the rest of the technical solutions are consistent with those in Example 2.
[0035] Technical indicator test The yields and performance index test results of tetrahydrofuran in Examples 1 to 3 and Comparative Examples 1 to 6 are shown in Table 1 below: Table 1 Purity (wt%) Water content (wt%) Yield (%) Transmittance (260nm) Example 1 ≥99.99 0.011 98.2 97.6% Example 2 ≥99.99 0.009 99.5 99.6% Example 3 ≥99.99 0.010 99.0 99.2% Comparative Example 1 99.95 0.026 95.3 95.6% Comparative Example 2 99.92 0.032 93.8 93.5% Comparative Example 3 99.90 0.046 88.2 88.3% Comparative Example 4 99.93 0.041 94.0 91.5% Comparative Example 5 99.95 0.025 97.2 97.0% Comparative Example 6 99.96 0.019 96.8 98.3% From the data comparison in Table 1 above, it can be seen that the chromatographic grade tetrahydrofuran prepared in Examples 1 to 3 of the present invention has excellent performance in multiple indicators such as purity, moisture, and yield. In particular, Example 2 has a purity of ≥99.99, which meets the requirements of chromatographic grade solvents, has a moisture content of only 0.009wt%, and a yield of up to 99.5, which has the advantages of high yield and high quality, and a transmittance (260nm) of up to 99.6%, indicating that the chromatographic grade tetrahydrofuran prepared by the method of the present invention has almost no scattering and absorption. It can be used for chromatographic analysis, which can be accurately controlled and efficiently performed, and the analysis results are more reliable.
[0036] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A production process for chromatographic grade tetrahydrofuran, characterized in that: The steps include: S1. Add 1,4-butanediol and catalyst into a round-bottom flask, install a short distillation column, stir magnetically, heat in an oil bath at 160-200°C, and evaporate the crude product while reacting; S2, washing the crude product obtained in step S1 with a sodium chloride aqueous solution and separating the organic layer liquid; S3, passing the organic layer liquid obtained in step S2 into an adsorbent column filled with an adsorbent for adsorption treatment to obtain chromatographic grade tetrahydrofuran.
2. A production process for chromatographic grade tetrahydrofuran according to claim 1, characterized in that: The preparation of the catalyst described in step S1 comprises the following steps: (1) Add carbon nanotubes to a three-necked flask, then add concentrated sulfuric acid and concentrated nitric acid to the three-necked flask in a volume ratio of 1 to 3:1, disperse evenly with ultrasound, condense and reflux in a constant temperature water bath at 80 to 100 ° C for 9 to 13 hours, cool to room temperature, add 3 to 5 times the volume of deionized water to dilute, stir and mix, centrifuge at 3000 to 5000 rpm for 16 to 20 minutes, wash with deionized water until neutral, and filter. Place the obtained solid in a vacuum drying oven and dry at 60 to 70 ° C to constant weight to obtain carboxylated carbon nanotubes for use; (2) Add 2,6-di-tert-butyl-4-aminophenol to anhydrous ethanol for ultrasonic dispersion, then add N,N-dimethylbenzylamine, continue ultrasonic dispersion until uniform, then heat to 50-70°C, add allyl isothiocyanate while stirring, stir at constant temperature for 5-6 hours, cool to room temperature, wash with water 3-5 times, place in a vacuum drying oven, dry at 30-40°C to constant weight to obtain hindered phenol for use; (3) adding carboxylated carbon nanotubes and hindered phenol into a reactor at a ratio of 1:1-3, reacting at 120-150°C for 0.5-1h, and obtaining modified carbon nanotubes for use; (4) The modified carbon nanotubes are uniformly dispersed in anhydrous ethanol, and then heteropoly acid is added, and the mixture is immersed at 50-60°C for 2-4 hours, and then dispersed for 30-50 minutes. The mixture is then placed in a rotary evaporator and subjected to rotary evaporation at 30-40°C. After most of the solvent is evaporated, the mixture is placed in a vacuum drying oven and dried at 30-40°C to constant weight to obtain the catalyst.
3. A production process for chromatographic grade tetrahydrofuran according to claim 2, characterized in that: The weight-to-volume ratio of the carbon nanotubes to the acid mixture in step (1) is 1 g:120-150 mL.
4. A process for producing chromatographic grade tetrahydrofuran according to claim 2, characterized in that: The mass ratio of 2,6-di-tert-butyl-4-aminophenol, N,N-dimethylbenzylamine and allyl isothiocyanate described in step (2) is 1:0.05-0.09:1-2.
5. A production process for chromatographic grade tetrahydrofuran according to claim 2, characterized in that: The mass volume ratio of the modified carbon nanotubes to anhydrous ethanol in step (4) is 1 g: 30-50 mL; The mass volume ratio of the modified carbon nanotubes to the heteropoly acid aqueous solution is 1 g:30-40 mL.
6. A production process for chromatographic grade tetrahydrofuran according to claim 2, characterized in that: The heteropoly acid described in step (4) is a Dawson structure heteropoly acid.
7. A process for producing chromatographic grade tetrahydrofuran according to claim 1, characterized in that: The method for preparing the adsorbent described in step S3 comprises the following steps: (1) Add chitosan to 1% acetic acid solution, stir until chitosan is completely dissolved, add activated carbon, stir at 80-90°C for 3-4 hours, let stand and filter, and then deep-cold grind at -80--20°C to obtain activated carbon-loaded chitosan composite for use; (2) Add the above activated carbon-loaded chitosan composite to isopropanol, raise the temperature to 80-90°C while stirring, add 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution, stir at constant temperature for 5-9 hours, filter, wash with anhydrous ethanol 3-5 times, filter, place in a vacuum drying oven, dry at 50-60°C to constant weight, and obtain the modified composite for use; (3) Dissolve acetamide and soybean lecithin in anhydrous ethanol at a weight ratio of 1:4-5 and mix well. Heat to 50-60°C and add the modified composite agent. Stir at constant temperature for 2-3 hours, filter and dry under vacuum at 30-40°C to obtain the adsorbent.
8. A process for producing chromatographic grade tetrahydrofuran according to claim 7, characterized in that: The weight volume ratio of chitosan to 1% acetic acid in step (1) is 1-2 g:100 mL; The weight ratio of chitosan to activated carbon is 1:40~100.
9. A process for producing chromatographic grade tetrahydrofuran according to claim 7, characterized in that: The mass volume ratio of the activated carbon-loaded chitosan composite agent to isopropanol described in step (2) is 1 g: 12-18 mL; The mass ratio of the activated carbon-loaded chitosan composite agent to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:0.3-0.
5.
10. A process for producing chromatographic grade tetrahydrofuran according to claim 7, characterized in that: The mass volume ratio of acetamide to anhydrous ethanol in step (3) is 1 g: 20-40 mL; The weight ratio of the acetamide to the modified composite agent is 1:80-120.
Citation Information
Patent Citations
Purification method of chromatographic-grade tetrahydrofuran
CN105085444A
Method for producing tetrahydrofuran
CN105228991A
Method for preparing a catalyst and method for producing 1,4-butanediol and / or tetrahydrofuran from furan
CN110997136A
Method for producing tetrahydrofuran
US20060122365A1